A socio-ecological approach to the determinants of animal health management: A scoping review - Lisa Vors; Fanny Debil; Legrand Saint-Cyr; Anthony Giacomini; Nicolas Fortané; Guillaume Lhermie (PLoS ONE, 2026)
With approximately 60% of human infectious diseases originating from zoonotic sources, an integrated approach to animal health management is critical. Significant barriers persist in optimizing disease control strategies, particularly regarding diagnostics, surveillance, biosecurity, and vaccination systems. Beyond technical and health-related aspects, socio-economic factors substantially influence both adoption and efficacy of intervention measures. While these determinants have been increasingly explored through integration of social sciences, such as economics, sociology, political science, into veterinary public health, most research remains confined to individual-level assessments focusing on epidemiological aspects and behavioral determinants, often neglecting broader social dynamics governing decision-making processes. Thus, this study develops a novel typology of determinants affecting the adoption of disease management measures using the socio-ecological model framework. We refer to these as “applicability factors”, defined as elements that either facilitate or hinder the implementation of animal health management measures. A scoping review was conducted to refine the classification of these factors, leading to the identification of 22,683 articles, of which 593 were analyzed. The scoping review was performed in accordance with the methodology defined by the PRISMA-ScR guidelines. Five key factors emerged: (1) individual and socio-cognitive, (2) socio-political and institutional, (3) economic, (4) organizational and professional, and (5) infrastructural. Our findings highlight critical barriers and facilitators while identifying research biases, including a predominant focus on zoonotic diseases and those with significant economic impact. The overrepresentation of studies from high-income countries underscores an imbalance in research efforts. Most studies emphasize individual-level determinants using epidemiological approaches, creating a notable gap in addressing systemic influences. Framing animal disease management within a socio-ecological model demonstrates the necessity of integrating these determinants into policy development. A systems-based approach proves essential for strengthening One Health governance. However, the current absence of cohesive and equitable global governance structures hampers strategy effectiveness. This calls for the implementation of intelligent governance mechanisms at local and global levels, coupled with appropriate tools and infrastructure to enhance disease management efficacy. The study provides a comprehensive framework for addressing multi-level determinants in animal health policy and practice.